Gambaran Deteksi Dini Kesehatan Sebagai Upaya Pencegahan Risiko Penyakit Berbasis Platform Kesehatan Digital - Ningsih, Kursiah Warti; Suryani; Kursiah Warti Ningsih; Rahmi Pramulia Fitri; Dwi Sapta Aryantiningsih; Winda Parlin; Roza Asnel; Tengku Hartian; Rahmat Saputra; Yoga Saputra; Mailiza Cahyani (IKES Payung Negeri Pekanbaru, 2025)
Early health detection is an important strategy in preventing disease risks in the community. Through routine health checks, disease risk factors can be identified early so that preventive interventions can be carried out appropriately. However, the utilization of early health detection services at the community level, especially in rural areas, is still not optimal. This study aims to describe early health detection as an effort to prevent disease risks in the community of Hamlet 1, Baru Village, Kampar Regency. This study is a descriptive study with a survey approach. The subjects were 312 heads of families domiciled in Hamlet 1, Baru Village, Kampar Regency. Data were collected through family data collection using a health platform that includes routine health check behavior for non-communicable diseases, early detection of cervical cancer, smoking behavior in the home, and infant immunization coverage by age group. Most families have not undergone routine health checks at least every 6 months, specifically abdominal circumference examinations (80.45%), early detection of cervical cancer (92.63%), blood sugar (59.62%), and cholesterol (58.97%). In addition, 43.27% of family members smoke in the home. Infant immunization coverage shows disparities across almost all age groups, particularly for follow-up immunizations such as PCV, Rotavirus, Influenza, MR, JE, Varicella, and Hepatitis A. The persistently low early detection of NCDs and suboptimal infant immunization coverage highlight the need to strengthen health education, increase access to services, and strengthen the role of families and health workers at the community level.